A critical analysis of stalking theory and implications for research and practice. (22nd September 2022) - Parkhill, Alice J.; Nixon, Margaret; McEwan, Troy E.
Abstract: This article comprehensively reviews and critiques theories providing an aetiological account of stalking. We evaluate applications of preexisting psychological theories to stalking (attachment theory, evolutionary theory, social learning theory, information processing models of aggression, coercive control theory, and behavioural theory) as well as the only novel theory of stalking to date: Relational goal pursuit theory. Our aim was to identify which are supported by research, identify gaps in theoretical scope and explanatory depth and examine how current theories might inform clinical practice. This evaluation suggests that theories of stalking are underdeveloped relative to other areas of forensic clinical psychology and the theoretical literature is relatively stagnant. Consequently, there is limited research into clinically meaningful constructs that can guide the assessment, formulation and treatment of this client group. We identify similarities across existing theories, discussing implications for future research and clinical practice with people who stalk.